Criminal Responsibility for Loan Collectors Who Commit Murder as a Forced Defense for Threats from Borrowers - Wirayuda, Wirayuda; Hayati, Mulida; Sangalang, Rizki Setyobowo (Dinasti Research, 2025)
Criminal liability against loan collectors who commit murder as a form of forced defense due to threats from borrowers. This study is motivated by the importance of legal protection for individuals who commit acts of self-defense in urgent situations, especially in the context of debt relations. The method used is normative juridical with statutory, conceptual, and comparative approaches. The results of the study show that acts of self-defense and forced defense that exceed the limit (noodweer excess) can be legally justified if they meet the elements of instantaneous attack, against the law, and proportional and forced action. In the case of loan collectors who are actually threatened, as in the case of MZ and AR, self-defense can be a reason for criminal expungement if it is proven that there is no intention to kill and the action is carried out under psychological pressure. Fair law enforcement requires careful analysis of the evidence, the psychological condition of the perpetrator, and the chronology of events so that the rights of perpetrators and victims are protected in a balanced manner.